2018
DOI: 10.1111/ggi.13225
|View full text |Cite
|
Sign up to set email alerts
|

Predicting survival of older community‐dwelling individuals according to five estimated glomerular filtration rate equations: The InChianti study

Abstract: The BIS equation discriminates the risk of all-cause mortality better than other equations in older community-dwelling individuals. The eGFR threshold under which mortality starts to increase could change as a function of the equation used. Geriatr Gerontol Int 2018; 18: 607-614.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Other biomarkers of kidney function, especially cystatin C, were investigated in an attempt to improve the accuracy of kidney function estimates. While the accuracy of equations including both creatinine and cystatin C in predicting measured GFR was found to be better than that observed with creatinine-based ones among older patients [15], the agreement between equations was found to be only marginally improved [16] and prognostic accuracy unchanged when adding cystatin C [17]. Thus, the additional costs generated by cystatin C assessment may not be associated with a true improvement in clinical assessment of kidney function.…”
Section: Introductionmentioning
confidence: 79%
“…Other biomarkers of kidney function, especially cystatin C, were investigated in an attempt to improve the accuracy of kidney function estimates. While the accuracy of equations including both creatinine and cystatin C in predicting measured GFR was found to be better than that observed with creatinine-based ones among older patients [15], the agreement between equations was found to be only marginally improved [16] and prognostic accuracy unchanged when adding cystatin C [17]. Thus, the additional costs generated by cystatin C assessment may not be associated with a true improvement in clinical assessment of kidney function.…”
Section: Introductionmentioning
confidence: 79%
“…However, a recent meta‐analysis showed that the strength of the association between metabolic syndrome and prognosis among older people might be higher when considering cardiovascular (RR 1.40, 95% CI 1.21–1.61) compared with all‐cause mortality (RR 1.17, 95% CI 1.07–1.28) . We only considered all‐cause mortality in our study, but we agree that investigating the impact of metabolic syndrome on the relationship between kidney function and all‐cause or cardiovascular mortality warrants future investigations.…”
Section: Disclosure Statementmentioning
confidence: 88%
“…Furthermore, we would like to clarify that the aim of our study was to compare the long‐term discriminative capacity of eGFR estimated by Chronic Kidney Disease Epidemiology Collaboration and Berlin initiative Study equations, either in the creatinine‐based or in the creatinine/cystatin C‐based forms, and by the full age spectrum equation with respect to mortality. Additionally, we also investigated whether the eGFR threshold at which the risk of mortality starts to increase might change as a function of the equation used . The main reason for doing this kind of analysis was to verify whether adding cystatin C (i.e.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Corsonello et al evaluated the predictive ability for all‐cause mortality by several estimated glomerular filtration rate (eGFR) equations in older people . The best indicator of discriminating all‐cause mortality was the Berlin Initiative Study equation, which was judged by sensitivity, specificity, areas under receiver operating curve analysis and C‐statistics.…”
mentioning
confidence: 99%